Authentic Immersion Versus Symbolic Exposure in Indonesian Language and Culture Education - Destiani Destiani; Yulianeta Yulianeta; Vismaia S. Damaianti; Yeti Mulyati; Isah Cahyani; Dian Anggraini; Muhammad Rudy (Universitas Islam Negeri Walisongo Semarang, 2025)
Intercultural learning is an important component in teaching Indonesian to foreign speakers (BIPA). The study aims to compare intercultural learning for foreign learners across four contexts: face-to-face in Indonesia, face-to-face in the learners' home countries, online, and the role of local teachers. Using a qualitative research design, data were collected through interviews, classroom observations, and questionnaires involving 22 foreign learners and 1 local teacher. The findings indicated that intercultural learning in Indonesia offers authentic cultural immersion and deep contextual understanding, while learning in home countries provided limited but practical exposure through workshops. Online learning allows flexible access to cultural materials, although understanding often remains symbolic. Local instructors act as cultural mediators but face limitations due to their practical experience. The study highlights the need to adjust learning strategies to include the Savoir framework by Byram (2020), promoting direct experiences and collaboration between local teachers and Indonesian communities abroad to enhance intercultural competence. Future researchers are encouraged to develop and evaluate Savoir-based intercultural curriculum models in diverse BIPA contexts, exploring how blended approaches combining in-country immersion, online tools, and locally trained instructors can enhance learners' intercultural competence.